2016
DOI: 10.1002/2016jd024873
|View full text |Cite
|
Sign up to set email alerts
|

How do green roofs mitigate urban thermal stress under heat waves?

Abstract: As the climate warms, heat waves (HWs) are projected to be more intense and to last longer, with serious implications for public health. Urban residents face higher health risks because urban heat islands exacerbate HW conditions. One strategy to mitigate negative impacts of urban thermal stress is the installation of green roofs (GRs) given their evaporative cooling effect. However, the effectiveness of GRs and the mechanisms by which they have an effect at the scale of entire cities are still largely unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 61 publications
(66 reference statements)
5
34
0
2
Order By: Relevance
“…This also brings up the question how efficiently the implementation of green roofs can be scaled up. Li et al [2014] and Sun et al [2016] describe a linear decrease of air temperature with green roof fraction, Mackey et al [2012] compare temperature reduction to the normalised difference vegetation index (NDVI) from satellite measurements and also find a linear relationship. However, this dependency is not well understood.…”
Section: Introductionmentioning
confidence: 92%
“…This also brings up the question how efficiently the implementation of green roofs can be scaled up. Li et al [2014] and Sun et al [2016] describe a linear decrease of air temperature with green roof fraction, Mackey et al [2012] compare temperature reduction to the normalised difference vegetation index (NDVI) from satellite measurements and also find a linear relationship. However, this dependency is not well understood.…”
Section: Introductionmentioning
confidence: 92%
“…geographic location, size, population density, building morphology, orography and surrounding land cover) a wide range of boundary‐layer characteristics need to be quantified. While modelling studies help explore the relative importance of enhanced roughness, anthropogenic heat, the urban heat island effect (Sun et al, ), orography, local circulation patterns, and synoptic conditions, observations to verify results remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…An important question is how NBS scale with implementation area, and how their effectiveness alone or in combination with grey infrastructure depends on their physical position in the landscape [84,93,94,116]. For example, a study of green roofs in Beijing, China, found that the reduction in UHI scaled linearly with green roof area: while 100% green roof coverage resulted in significant city-wide cooling (1.5°C), 10% green roof coverage led to only 0.1-0.2°C cooling [124]. On the other hand, a study in Madison (Wisconsin, USA) found that temperature was related to tree canopy cover in nonlinear ways that depended on impervious cover, spatial scale and time of day (daytime versus night-time) [91].…”
Section: Research Prioritiesmentioning
confidence: 99%